Validation of chromatography data systems : meeting business and regulatory requirements - McDowall, R. D. (RSC chromatography monographs., 2005)
Chromatography is a major analytical technique that is used throughout research, development and manufacturing in the pharmaceutical, medical device and associated industries. To demonstrate fitness for purpose with the applicable regulations, the systems must be validated. Validation of Chromatography Data Systems: Meeting Business and Regulatory Requirements introduces the basics of computer validation. It looks in detail at the requirements throughout the life cycle of a CDS for any regulated laboratory, from its concept, through writing the user requirements specification to selecting the system, testing and operational release, including using electronic signatures. This logical and uniquely organised book provides the background to the regulatory requirements, interpretation of the regulations and documented evidence needed to support a claim that a system is validated. Development of the system, risk management, operation and finally system retirement and data migration are discussed. Case studies and practical examples are provided where appropriate. Validation of Chromatography Data Systems: Meeting Business and Regulatory Requirements is ideal for the chromatographer working in analytical laboratories in the regulated pharmaceutical, contract research, biotechnology and medical device industries seeking the practical guidance required for validating their chromatography data systems in order to meet regulatory requirements. It will also be welcomed by consultants or those in regulatory agencies.